The Implementation of Health Promotion Concept During the Covid-19 Pandemic: The Case of the Neighborhood Alert Program in Surabaya City, Indonesia - Soedirham, Oedojo; Putra, Muhammad Baharuddin Wisudawan (Advances in Social Sciences Research Journal, 2022)
Coronavirus disease 2019 (Covid-19) is a disease caused by a virus from the Coronavirus group. Covid-19 has spread to almost all parts of the world and has increased the number of accumulative cases continuously to date. In Indonesia, East Java Province is one of the provinces with the highest cumulative confirmed cases of Covid-19. This problem has prompted the government to make efforts to contain Covid-19. Covid-19 Task Force Neighborhood Association Alert is a form of collaboration between Healthcamp.id and the Provincial Government of East Java through the East Java Covid-19 Task Force to promote health with a community approach within the Neighborhood Association. Therefore, one of the authors participated in this activity in helping to prevent and overcome Covid-19 in East Java Province, especially in the City of Surabaya. Volunteer activities are participatory observational with online and offline methods. Volunteer activities were carried out on 12 May 2020 - 2 July 2020. Volunteers made various efforts to tackle Covid-19, including health education, health screening, data collection of aid, monitoring of citizen health, monitoring of residents' territorial conditions, and distributing aid. These activities are then analyzed and evaluated based on what is health promotion action means. This activity concludes that all efforts to combat Covid-19 have been carried out according to the program. It is known that the knowledge of residents in the Neighborhood Association (NbA) Alert the City of Surabaya program area is mostly good with the implementation of the Covid-19 health protocol, namely as many as 99% of respondents. The attitude of residents in the NbA Alert the City of Surabaya program area is good with the protocol for implementing the Covid-19 health, which is 100% of respondents. Most of the actions of residents in the NbA Alert the City of Surabaya program area have been good with the implementation of the Covid-19 health protocol, namely as many as 97% of respondent.